2023
DOI: 10.3390/jcm12155143
|View full text |Cite
|
Sign up to set email alerts
|

Use of Artificial Intelligence in the Advancement of Breast Surgery and Implications for Breast Reconstruction: A Narrative Review

Abstract: Background: Breast reconstruction is a pivotal part of the recuperation process following a mastectomy and aims to restore both the physical aesthetic and emotional well-being of breast cancer survivors. In recent years, artificial intelligence (AI) has emerged as a revolutionary technology across numerous medical disciplines. This narrative review of the current literature and evidence analysis explores the role of AI in the domain of breast reconstruction, outlining its potential to refine surgical procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Algorithms can analyze vast amounts of ultrasound data, identifying subtle patterns and predicting outcomes. In breast reconstruction, researchers are currently exploring the use of AI systems to analyze ultrasound images and identify potential anomalies such as tumors or vascular abnormalities, as well as to assist with preoperative planning, intra-operative decision making and precision enhancement, and postoperative monitoring [ 67 ]. Advanced machine learning techniques, including the Faster-RCNN model with the Inception-ResNet-v2 architecture for analyzing ultrasound breast images, have fine-tuned these procedures and demonstrate promise for integration into surgical practices.…”
Section: Discussionmentioning
confidence: 99%
“…Algorithms can analyze vast amounts of ultrasound data, identifying subtle patterns and predicting outcomes. In breast reconstruction, researchers are currently exploring the use of AI systems to analyze ultrasound images and identify potential anomalies such as tumors or vascular abnormalities, as well as to assist with preoperative planning, intra-operative decision making and precision enhancement, and postoperative monitoring [ 67 ]. Advanced machine learning techniques, including the Faster-RCNN model with the Inception-ResNet-v2 architecture for analyzing ultrasound breast images, have fine-tuned these procedures and demonstrate promise for integration into surgical practices.…”
Section: Discussionmentioning
confidence: 99%
“…While intraoperative AI assistance has not been extensively explored in breast reconstruction, AI aids postoperative care through early complication detection, predicting complications, and assessing postoperative pain. In a retrospective study conducted by Zhu et al, the multifactor AI model developed by their team showed remarkable effectiveness in identifying axillary lymph node metastasis, marking a breakthrough in surgical research [ 41 ]. Notably, the study introduced an AI-supported surgical approach that significantly enhanced the model's accuracy compared to the conventional sentinel lymph node biopsy method alone.…”
Section: Reviewmentioning
confidence: 99%
“…For its part, artificial intelligence can enhance both 3D and 4D printing by aiding decision making during preoperative planning, simplifying material selection and streamlining production processes [ 103 , 104 ].…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%